Systematic Exploration of a Catalytic Metal–Organic Framework/Polyurethane Composite for Medical Device Applications: Effects of MOF Particle Size, MOF Loading, and Polymer Concentration on Composite Material Activity - Melvin, Alyssa C.; Reynolds, Melissa M. (Frontiers in Physics, 2022)
The metal–organic framework (MOF) CuBTTri, H3[(Cu4Cl)3(BTTri)8] (where H3BTTri = 1,3,5-tris(1H-1,2,3-triazol-5-yl)benzene), is a promising catalyst for the development of antithrombotic medical device materials via localized nitric oxide (NO) generation from endogenous S-nitrosothiols. One way to incorporate MOFs into devices is by embedding them within polymers; however, it is currently unknown how composite material parameters will impact the level of observed NO generation catalyzed by the embedded CuBTTri particles. This work evaluates three key parameters of composite materials—MOF preparation/particle size, MOF loading, and polymer concentration—using composite films comprised of CuBTTri and a medical-grade hydrophilic polyurethane, Tecophilic SP-80A-150. We discovered that CuBTTri preparation and particle size have a significant impact on NO generation. Specifically, hand ground MOF particles (0.3 ± 0.1 µm diameter) generate NO at greater rates compared to larger as-prepared, raw MOF particles (0.4 ± 0.2 µm diameter) and smaller, filtered MOF particles (0.2 ± 0.1 µm diameter) for composite materials. This finding contradicts previous research for CuBTTri powder which found that the smaller the particles, the greater the catalytic rate. Our data also show that, in general, increasing both MOF loading and polymer concentration results in increased rates of NO generation; though thresholds appear to exist in which increasing these parameters results in diminishing returns and impedes NO generation capacity for certain composite formulations. The unique water absorptivity metric for each MOF/polymer combination is also a contributing factor in MOF composite activity. This research provides a framework for more strategic selections of key parameters when fabricating composite materials for medical device applications.